Routine Multimodal Antiemesis Including Low-Dose Perphenazine in an Ambulatory Surgery Unit of a University Hospital: A 10-Year History - Brian A. Williams; Michael L. Kentor; Susan J. Skledar; Steven L. Orebaugh; Manuel C. Vallejo (The Scientific World Journal)
For 10 years, we have used intravenous and oral perphenazine as part of a multimodal antiemetic prophylaxis care plan for at least 10,000 outpatients. We have never encountered an adverse event, to our knowledge, when the intravenous dose was less than or equal to 2 mg, or when the single preoperative oral dose did not exceed 8 mg (with no repeated dosing). As a single-dose component of multimodal antiemetic prophylaxis therapy, we believe that this track record of anecdotal safety in adults who meet certain criteria (age 14–70, no less than 45 kg, no history of extrapyramidal reactions or of Parkinson disease, and no Class III antidysrhythmic coadministered for coexisting disease) constitutes a sufficient patient safety basis for formal prospective study. We believe that future perphenazine studies should include routine coadministration with prospectively established multimodal antiemetics (i.e., dexamethasone and a 5-HT3 antagonist). In settings where droperidol is still routinely used and deemed acceptable by local scientific ethics committees, we believe that oral perphenazine 8 mg should be compared head to head with droperidol 0.625–1.25 mg in patients receiving coadministered dexamethasone and 5-HT3 antagonists in order to determine differences in synergistic efficacy, if any. Similar trials should be performed, individually evaluating cyclizine, transdermal scopolamine, and aprepitant in combination with coadministered dexamethasone and a 5-HT3 antagonist. Such studies should also quantify efficacy in preventing nausea and vomiting after discharge home, and also quantify the extent to which the prophylaxis plans reduce postanesthesia care unit (PACU) requirements (i.e., increase PACU bypass), reduce the need for any nursing interventions for postoperative nausea and/or vomiting (PONV), and influence the extent to which any variable costs of postoperative nursing care are reduced.